Closing the gap in emergency medicine: enhancing EMS communication through a Spanish communication badge and patient rights pamphlet - McLaughlin, Avery, author; Miller De Rutté, Alyssia, advisor; Correa, Maite, committee member (Colorado State University. Libraries, 2026)
Language barriers in emergency medical settings result in consequences greater than a simple miscommunication. Communication gaps between providers and patients complicate care coordination, decrease quality of care, and lower overall patient satisfaction, leaving patients underserved in systems designed to protect them. To combat these challenges, a quick, Spanish communication badge and patient rights pamphlet were developed with the intent of assisting emergency medical services (EMS) personnel in emergency encounters with Spanish-speaking patients. A three-part methodological approach was used to obtain data, focusing on independent literature review, formal coursework, and primary data collection. Findings from all three sources were utilized to guide the content, formatting, and design of the final badge and patient rights pamphlet. The primary outcome of this project is a physical communication badge tool designed for use by EMS personnel during encounters with Spanish-speaking patients with limited English proficiency and an accompanying patients rights pamphlet. Phrases on the badge are provided in English and Spanish, with phonetic spelling found below each Spanish phrase, making the tool accessible to providers with no prior Spanish experience. The patient rights pamphlet, written entirely in Spanish, complements the badge by providing Spanish-speaking patients and their families with accessible information about their rights during an EMS encounter, in a hospital, and average cost of emergency services. Together, the badge and pamphlet function as coordinated tools to address both provider and patient needs, equipping providers with tools to communicate as accurately as possible and equipping patients with the knowledge to understand and exercise their rights. This approach is a start to addressing care gaps for Spanish-speaking patients, and demonstrates that improving care for underserved populations requires not only providers willing to communicate in another language, but greater encouragement for patients themselves to meaningfully participate in their own care.